Geração de curvas de roteamento para redes de sensores sem fio - Olga Nikolaevna Goussevskaia (2005)
Beyond today's embedded technology, next generation micro sensors incorporating wireless technology will be able to cost-effectively connect large numbers of tiny, inexpensive devices, originating the WirelessSensor Networks (WSNs), sometimes called .smart dust.. This technology will enable new kinds of pervasive computing and smart environments The routing problem in WSNs is often called .data dissemination.. An interesting data dissemination technique is trajectory-based forwarding. The innovation of this approach consists in representing the route as a continuous function, instead of a set of discrete points. The main idea is to embed a curve equation into the packet header and let the intermediate nodes forward it to nodes located close to the curve. This technique is immune to changes in network connectivity and is scalable to the size of the network and the number of nodes comprising the route. Trajectory-based forwarding assumes there is a mechanism to generate the trajectories. However, as far as we know, the problem of trajectory generation has not been addressed in the literature. In this work, a method to dynamically generate routing curves based on the energy map of the network is proposed. Simulation results reveal that the energy spent with data disseminationactivity can be concentrated on node with high energy reserves, whereas lowenergy nodes can use their energy only to perform sensing activity. In thismanner, partitions of the network due to nodes that run out of energy can be signicantly delayed and the network lifetime extended.The contributions of this thesis were published in IEEE CommunicationsMagazine (Ad Hoc and Sensor Networks Series) [11] and Journal on Selected Areas in Communication (Special Issue on Autonomics) [8].